2015
DOI: 10.4028/www.scientific.net/kem.656-657.28
|View full text |Cite
|
Sign up to set email alerts
|

Development of Recovery System for Extracting Silicon Carbide from Photovoltaic Industry Abrasive Slurry

Abstract: Silicon carbide (SiC) is widely employed as an abrasive material in aqueous media for sawing silicon ingot into individual wafers in photovoltaic industry. After a series of cutting, grinding and polishing operation, a mixture of substances (Cutting fluid, SiC, Si and small amount of magnetic metal) is produced as a form of slurry. The used SiC can be preferably recovered and reused for another application, rather than disposed of as waste. In this study, a pilot scale system (25 kg/h) is developed to extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Both powders are mixed with a stoichiometric ratio of SiC and then pressed using a uniaxial hot-pressed at 180°C by applying [216] have used shungite (amorphous coal) and steel plant wastes, respectively, to fabricate SiC. Additionally, some studies are found that the recovering of SiC from photovoltaic industry waste [217,218] and Si wafer cutting slurry [219][220][221][222] through different filtration processes like flotation, applied electrical field, hydrocyclone separation, and alkali-acid treatment.…”
Section: Silicon Carbidementioning
confidence: 99%
“…Both powders are mixed with a stoichiometric ratio of SiC and then pressed using a uniaxial hot-pressed at 180°C by applying [216] have used shungite (amorphous coal) and steel plant wastes, respectively, to fabricate SiC. Additionally, some studies are found that the recovering of SiC from photovoltaic industry waste [217,218] and Si wafer cutting slurry [219][220][221][222] through different filtration processes like flotation, applied electrical field, hydrocyclone separation, and alkali-acid treatment.…”
Section: Silicon Carbidementioning
confidence: 99%